Conditions for extracting photoionization cross sections from laser-induced high-order-harmonic spectra - Wang, Guoli; Jin, Cheng; Le, Anh-Thu; Lin, C. D. (My University, 2012)
We show that photoionization cross sections of atoms can be accurately extracted from the high-order-harmonic spectra generated by intense infrared lasers only if the degree of ionization in the gas medium is small, implying that for this purpose the high-order-harmonic generation spectra should be taken at low gas pressure and at low laser intensity experimentally.